The Building Gender Balance: Reviewing the Capacity Enhancement of Women Legislators in Lumajang Regency - Eny Nurwahyuni; Bambang Tri Sasongko Adi; Oman Sukmana; Vina Salviana D. Soedarwo (Eduvest - Journal of Universal Studies, 2025)
This study examines the importance of enhancing the capacity of women before running as legislative candidates in Lumajang Regency by analyzing the Women's Empowerment Index, Gender Index, and educational status of female legislators. The identified problem is that although parties meet a 30% quota for female candidates, this is often viewed as a formal requirement without strong support to ensure their election. The study aims to highlight the need for capacity-building prior to candidacy and propose concrete steps to improve it. Using a descriptive approach with secondary data analysis, the research reviews journals, statistical data, and media reports on women's legislative capacity in Lumajang. The Likert scoring method (1–5) assesses capacity in political knowledge, education, diplomatic skills, and concern for development. Results indicate gender-responsive planning is fairly well implemented but reveal significant gaps in education and institutional support. Female legislators' capacity is adequate but needs improvement, especially in education, diplomacy, and development knowledge. Only two of five female legislators hold bachelor’s degrees; the rest have only high school education, showing an educational gap that hinders effectiveness. Recommendations include increasing access to higher education, continuous training, optimizing empowerment programs, and ensuring that female candidate quotas come with concrete support. This study’s implications strengthen women’s representation and promote gender balance in local politics, contributing to more inclusive and effective governance in Lumajang Regency.